(3OjhGf GdHMJQis - (3GdHMJQj , CHh YHGOI GdhdjO Hf YHjO Hf jMji GdWGFj GdHMJQj, GdHMJQj,J (B284 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jMSf TjA EdG jchf MeOg GHJOGDg hdG jced TjA MJi jQi TcQg GfJgGDg s
(3BNQgG (B:s
(3gPG BNQ GdefJbi ef OjhGf CHj QLGA (B((3cPG(B) (3GdTGYQ GdeYQha HGdHMJQi GdMeO ddg hMOg s
(3HgG fXGe GdJYbjHIs
(3Ydi dhMI GdYfhGf hGdhQbI GdChdi JedcGJs
(3JHUQI GdYfhGf (B:s
(3EfJbGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B141s
Keywords: (3GdCOHs